Regulation of MHC II and CD1 antigen presentation: from ubiquity to security - Gelin, Catherine; Sloma, Ivan; Charron, Dominique; Mooney, Nuala (Journal of leukocyte biology, 2009)
MHC class II and CD1‐mediated antigen presentation on various APCs [B cells, monocytes, and dendritic cells (DC)] are subject to at least three distinct levels of regulation. The first one concerns the expression and structure of the antigen‐presenting molecules; the second is based on the extracellular environment and signals of danger detected. However, a third level of regulation, which has been largely overlooked, is determined by lateral associations between antigen‐presenting molecules and other proteins, their localization in specialized microdomains within the plasma membrane, and their trafficking pathways. This review focuses on features common to MHC II and CD1 molecules in their ability to activate specific T lymphocytes with the objective of addressing one basic question: What are the mechanisms regulating antigen presentation by MHC II and CD1 molecules within the same cell? Recent studies in immature DC, where MHC II and CD1 are coexpressed, suggest that the invariant chain (Ii) regulates antigen presentation by either protein. Ii could therefore favor MHC II or CD1 antigen presentation and thereby discriminate between antigens.